A FPGA-based Cluster Finder for CMOS Monolithic Active Pixel Sensors of the MIMOSA-26 Family - Li, Qiyan; Amar-Youcef, S; Doering, D; Deveaux, M; Fröhlich, I; Koziel, M; Krebs, E; Linnik, B; Michel, J; Milanovic, B; Müntz, C; Stroth, J; et al. (Journal of physics. Conference series, 2014)
CMOS Monolithic Active Pixel Sensors (MAPS) demonstrated excellent performances in the field of charged particle tracking. Among their strong points are an single point resolution few μm, a light material budget of 0.05% X0 in combination with a good radiation tolerance and high rate capability. Those features make the sensors a valuable technology for vertex detectors of various experiments in heavy ion and particle physics. To reduce the load on the event builders and future mass storage systems, we have developed algorithms suited for preprocessing and reducing the data streams generated by the MAPS. This real-time processing employs remaining free resources of the FPGAs of the readout controllers of the detector and complements the on-chip data reduction circuits of the MAPS.